2017
DOI: 10.18203/2394-6040.ijcmph20174840
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of ambulation potential with quality of life in lower limb amputees

Abstract: Background: To identify the effect of walking ability on quality of life in lower limb amputees and draw a correlation between prosthesis use, socio economic status and quality of life. It was an Observational Cross sectional study.Methods: Lower limb amputees excluding hip disarticulation and bilateral lower limb amputation, individuals above eighteen years of age who attended rehabilitation research centre outpatient door were interviewed. Structured questionnaire including patient background, amputation cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
4
4
0
Order By: Relevance
“…According to the type of amputation the present study results revealed that 37% had a below knee leg amputation. This is consistent with the study conducted by (Agrawal et al, 2017) in which they founded that total individuals with below knee amputation were 340(70.69%) followed by above knee amputation 127(26.40%) and trans knee amputation 14 (2.91%). This is explained by the fact that it is a general opinion all over the world amongst surgeons to save as much limb as possible to allow maximum mobility for greater independence.…”
Section: Types Of Amputationsupporting
confidence: 92%
“…According to the type of amputation the present study results revealed that 37% had a below knee leg amputation. This is consistent with the study conducted by (Agrawal et al, 2017) in which they founded that total individuals with below knee amputation were 340(70.69%) followed by above knee amputation 127(26.40%) and trans knee amputation 14 (2.91%). This is explained by the fact that it is a general opinion all over the world amongst surgeons to save as much limb as possible to allow maximum mobility for greater independence.…”
Section: Types Of Amputationsupporting
confidence: 92%
“…Numerous studies place trauma as a leading cause of lower limb amputation [ 26 , 27 ] second only to complicated diabetes [ 28 ]. In addition to literature shows that the trauma (65.49%) followed by infection (25.16%) as the most common indication of amputation [ 29 ] and the lower extremity injuries contribute to over half of all war injuries, resulting in permanent disability [ 30 ]. The results of our study can be explained by the fact that the majority of the individuals, were soldiers injured in combat.…”
Section: Discussionmentioning
confidence: 99%
“…Medical co-morbidities, the amount of amputation, cognitively, age, which was before level of function, social protection, environmental circumstances, and economic ability are only a few of the linked factors that impact functional outcome after amputation. Individual psychological and cognitive well-being, social support, financial position, and a variety of prosthesis-related variables all impact on rehabilitation outcomes (Agrawal et al, 2017).…”
Section: Ennion and Johannesson 2018)mentioning
confidence: 99%